Moderators of psychological and psychoeducational interventions for the prevention of depression: A systematic review. - Conejo-Cerón, Sonia; Bellón-Saameño, Juan Ángel; Motrico, Emma; Campos-Paíno, Henar; Martín-Gómez, Carmen; Ebert, David D.; Buntrock, Claudia; Gili, Margalida; Moreno-Peral, Patricia (Elsevier, 2020)
Psychological and psychoeducational interventions have proven to be effective in preventing depression. However, the identification of the patients that benefit the most from each type of intervention has not yet been established. A systematic review was performed of the literature on moderators of preventive psychological and psychoeducational interventions for depression in all types of population. A search was performed on PubMed, PsycINFO, Web of Science, Embase, Cochrane Central Register of Controlled Trials and OpenGrey up to July 2019. Fulfillment of eligibility criteria, data collection, and study quality assessment were assessed by two independent researchers. Outcomes were moderators of the reduction of depressive symptoms or the incidence of depression. Twenty-seven moderator effect studies performed in 19 randomized controlled trials were included. Thirty-four potential sociodemographic, clinical, interpersonal, personality and life-event moderators were evaluated. Baseline depressive symptoms, gender, age, baseline parental depression and social support were the most frequently studied potential moderators. In interventions for children and adolescents, the moderator for which evidence was strongest was having parents free of depression at baseline. Psychological and psychoeducational interventions seem to be more effective in children and adolescents who exhibit a lower use of substances and whose parents do not have symptoms of depression at baseline. In adults, a lower age was associated with greater effects of preventive interventions.
https://openpolicyfinder.jisc.ac.uk/id/publication/15169
Keywords: Depresión mental - Prevención; Revisiones sistemáticas (Medicina); Depression; Moderator; Prevention; Systematic review